Auditor Quality and the Accuracy of Management Earnings Forecasts - CLARKSON, PETER M.; Queensland, The University of (Contemporary Accounting Research, 2000)
In this study, we appeal to insights and results from Davidson and Neu 1993 and McConomy 1998 to motivate empirical analyses designed to gain a better understanding of the relationship between auditor quality and forecast accuracy. We extend and refine Davidson and Neu's analysis of this relationship by introducing additional controls for business risk and by considering data from two distinct time periods: one in which the audit firm's responsibility respecting the earnings forecast was to provide review-level assurance, and one in which its responsibility was to provide audit-level assurance. Our sample data consist of Toronto Stock Exchange (TSE) initial public offerings (IPOs). The earnings forecast we consider is the one-year-ahead management earnings forecast included in the IPO offering prospectus. The results suggest that after the additional controls for business risk are introduced, the relationship between forecast accuracy and auditor quality for the review-level assurance period is no longer significant. The results also indicate that the shift in regimes alters the fundamental nature of the relationship. Using data from the audit-level assurance regime, we find a negative and significant relationship between forecast accuracy and auditor quality (i.e., we find Big 6 auditors to be associated with smaller absolute forecast errors than non-Big 6 auditors), and further, that the difference in the relationship between the two regimes is statistically significant.